Presentation. Environment and sustainability in micro perspective - Camacho Monge, Daniel (2023)
In our central theme entitled “ENVIRONMENT AND SUSTAINABILITY IN MICRO PERSPECTIVE” we propose specific cases of processes related to environmental challenges. There are quite a few studies, although they will never be enough, on the topic of the environment from a macro perspective. It is necessary, however, to keep in mind how this same issue develops in micro spaces,  where the processes that damage or preserve nature ultimately occur. To illustrate this topic we have chosen four articles.